Peningkatan Efisiensi Administrasi dengan Implementasi Perangkat Digital OSS dalam Pembuatan Nomor Induk Berusaha pada UMKM Menyenk Cafe - Nur Fadia Ulfa; Ratih Mukti Azhar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
This study aims to evaluate the administrative efficiency of the Online Single Submission (OSS) digital tool in making a Business Identification Number (NIB) for Micro, Small and Medium Enterprises (MSMEs) in Tenggilis Mejoyo Village. Law number 20 of 2008 provides a clear definition of MSMEs, while licensing requirements are regulated to prevent market failure. MSMEs in this area have an important role in economic development and community empowerment, with diverse business sectors. This research used three data collection techniques: observation, interview, and documentation. The owner of Menyenk Cafe became the subject who received socialisation and hands-on training. The flow of community service activities involves data collection, problem analysis, implementation, and socialisation of NIB training. With a focus on MSMEs at Menyenk Cafe, this research details the steps of data collection through literature studies, observations, interviews, and documentation. The results of the research are expected to provide input for the government, business actors, and the community regarding the effectiveness of OSS in improving the efficiency of business licensing administration.